Functional Implications of the CLOCK 3111T/C Single-Nucleotide Polymorphism - Ozburn, Angela R.; Purohit, Kush; Parekh, Puja K.; Kaplan, Gabrielle N.; Falcon, Edgardo; Mukherjee, Shibani; Cates, Hannah M.; McClung, Colleen A. (Frontiers in Psychiatry, 2016)
Circadian rhythm disruptions are prominently associated with Bipolar Disorder (BD). Circadian rhythms are regulated by the molecular clock, a family of proteins that function together in a transcriptional-translational feedback loop. The CLOCK protein is a key transcription factor of this feedback loop, and previous studies have found that manipulations of the Clock gene are sufficient to produce manic-like behavior in mice (Roybal et al., 2007). The Clock 3111T/C single-nucleotide polymorphism (SNP; rs1801260) is a genetic variation of the human Clock gene that is significantly associated with increased frequency of manic episodes in BD patients (Benedetti et al., 2003). The 3111T/C SNP is located in the 3’ untranslated region of the Clock gene. In this study, we sought to examine the functional implications of the human Clock 3111T/C SNP by transfecting a mammalian cell line (mouse embryonic fibroblasts isolated from Clock -/- knockout mice) with pcDNA plasmids containing the human Clock gene with either the T or C SNP at position 3111. We then measured circadian gene expression over a 24 hour time period. We found that the Clock3111C SNP resulted in higher mRNA levels than the Clock 3111T SNP. Further, we found that Per2, a transcriptional target of CLOCK, was also more highly expressed with Clock 3111C expression, indicating the 3’UTR SNP affects the expression, function and stability of Clock mRNA.